(untitled) (Bioscience Journal, 2023)
The work aimed at determining the effects of applying different blends between liquid molasses and agricultural limestone on water quality and growth performance of Nile tilapia juveniles, Oreochromis niloticus. The study employed 24 indoor tanks of 100 L and 24 outdoor tanks of 250 L. Four control groups were set up (no product applied, only molasses, only limestone, molasses-limestone blend with 48% limestone but no fish) and two experimental groups (molasses-limestone blends with 32% and 48% molasses), with four replicates each. Over 11 weeks, the water quality was monitored systematically. The 24-h cycle monitoring of temperature, pH, specific conductance, dissolved O2 and total alkalinity were carried out at the 8th week. The blends between molasses and limestone accelerated the dissolution rate of the agricultural limestone in water. The blend containing 48% molasses led to greater increases in water alkalinity and pH in relation to tanks with only limestone applications. However, the molasses-limestone blend applications impaired the Nile tilapia growth performance, especially in the outdoor tanks. While the fish yield was 25.1 g m-3 day-1 in the molasses outdoor tanks, it was equal to 22.8 g m-3 day-1 in the molasses (32%)-limestone units (P<0.05). It has been concluded that the blending between limestone and molasses brings no clear benefits to Nile tilapia’s rearing tanks when compared to the limestone-only tanks.